2020
DOI: 10.21203/rs.3.rs-17123/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation between immune-related adverse events and prognosis in patients with various cancers treated with anti PD-1 antibody.

Abstract: Background: Immune checkpoint inhibitors (ICIs) targeting programmed cell death protein 1 (PD-1) are used for the treatment of various cancer types. However, immune-related adverse events (irAEs) occur in patients treated with ICIs. Several small-scale studies have reported the onset of irAEs and therapeutic effects of ICIs. Here we report a large-scale retrospective study covering a wide range of cancers. We evaluated irAEs and the therapeutic effects of ICIs and determined whether irAEs could be predicted.Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Matsuoka H, et al recently analyzed a cohort with various types of cancer including MPM, and showed that ORR, OS and PFS were signi cantly better in the patients with irAEs than in those without irAEs. 19 Although this cohort included only four MPM patients in total 260 cases, none of them developed irAEs, therefore, it was still unclear whether there is a correlation between irAEs and therapeutic effect in patients with MPM. In this study, we examined the eight patients with MPM, and showed the PFS in the patients with irAEs was signi cantly longer than their counterpart.…”
Section: Discussionmentioning
confidence: 95%
“…Matsuoka H, et al recently analyzed a cohort with various types of cancer including MPM, and showed that ORR, OS and PFS were signi cantly better in the patients with irAEs than in those without irAEs. 19 Although this cohort included only four MPM patients in total 260 cases, none of them developed irAEs, therefore, it was still unclear whether there is a correlation between irAEs and therapeutic effect in patients with MPM. In this study, we examined the eight patients with MPM, and showed the PFS in the patients with irAEs was signi cantly longer than their counterpart.…”
Section: Discussionmentioning
confidence: 95%
“…Recent reports from the clinical literature have demonstrated a positive correlation between the onset of immune-related adverse events (irAEs) and the tumor response to ICI (73)(74)(75), suggesting that effective IO therapy should be reflected and manifest proximal to the TIME. In line with this observation, we found that lymphatic-sparing treatment sequencing activated both regional and peripheral host antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports from the clinical literature have demonstrated a positive correlation between the onset of immune-related adverse events (irAEs) and the tumor response to ICI [77][78][79] , suggesting that effective IO therapy should be reflected and manifest proximal to the TIME. In line with this observation, we found that lymphatic-sparing treatment sequencing activated both regional and peripheral host antitumor immunity.…”
Section: Discussionmentioning
confidence: 99%